Diagnosis of toxoplasmosis in pregnancy. Evaluation of latex–protein complexes by immnunoagglutination. Issue 8 (14th March 2017) - PERETTI, LEANDRO E.; GONZALEZ, VERÓNICA D. G.; MARCIPAR, IVÁN S.; GUGLIOTTA, LUIS M.
SUMMARY: The aim of this work was to obtain a reagent based on latex particles for ruling out acute toxoplasmosis in pregnant women by immunoagglutination (IA). Latex–protein complexes (LPC) were previously synthesized coupling the recombinant protein of Toxoplasma gondii P22Ag and the homogenate of the parasite to latex particles with different size, chemical functionality and charge density. LPC were tested in IA assays against a panel of 72 pregnant women serum samples. Results were analysed through receiver operating characteristic curves, determining area under the curve (AUC), sensitivity, specificity positive and negative predictive values (PPV and NPV, respectively). It was observed that the antigenicity of proteins was not affected during sensitization by either physical adsorption or covalent coupling. The best results in the sense of maximizing discrimination of low avidity sera from chronic ones were observed for the IA test based on latex particles with carboxyl functionality and the recombinant P22Ag, obtaining an AUC of 0·94, a sensitivity of 100% and a NPV of 100%. In this way, the proposed test could be useful for the toxoplasmosis diagnosis in pregnant women, with the advantages of being cheap, rapid and easy to be implemented.